The Impact of Liquidity on the Financial Performance of Banks Listed on the Indonesia Stock Exchange (IDX) - Erina Yanti; Pu Libing; Henny Setyo Lestari; Susy Muchtar (Universitas KH. Abdul Chalim Mojokerto, 2026)
This research seeks to examine the impact of credit risk, liquidity, price risk, operational risk, capital adequacy ratio, and loan-to-deposit ratio on the financial performance of banks listed on the Indonesia Stock Exchange (IDX) during 2020–2024. Financial performance is assessed through ROA and ROE. Using purposive sampling, 26 banks that met the criteria were selected and analyzed through panel data regression. The results suggest that companies and investors should also take into account other factors that may influence financial performance. The regression analysis revealed that, individually, the LDR and operational risk (ORISK) significantly affected ROA, while the remaining variables were not significant. However, collectively, all independent variables had a significant impact on ROA, with an adjusted R-squared of 65%, indicating that 65% of ROA variation was explained by these variables. In contrast, for the ROE model, only operational risk (ORISK) showed a significant partial effect, whereas other variables were insignificant. Simultaneously, the independent variables significantly influenced ROE, with an adjusted R-squared of 54%, meaning that 54% of the variation in ROE was accounted for. Overall, operational risk (ORISK) consistently exerted a negative influence on bank profitability under both ROA and ROE measures, whereas the effects of other variables were more limited. These results highlight the critical role of operational risk management in sustaining banking profitability.